Mobile Instant Messaging Communication Etiquette: Educators’ Voices and Point of View - Alfelia Nugky Permatasari; Endang Soelistiyowati; Vincentius Tangguh Atyanto Nugroho (PAROLE: Journal of Linguistics and Education, 2022)
Communication using digital media has highly increased since the pandemic, including within education context. Different types of expectation between the involved parties sometimes causing communication challenge for both.  This study aims to find out how educators viewed the courtesy shown by the students during interactions using instant messaging media. Specifically, it aims to find out politeness indicators, communication challenges, and educators’ expectations. The interview questions included the concept of appropriate and polite messages between students as well as the overall attitudes of students within WhatsApp communication. The interviews are transcribed and coded based on what is listed in the framework. The results of the study reveal that most lecturers agreed students are adept in establishing communication through WhatsApp, compared to those in the past by incorporating greetings to open a conversation, stating identity, thanking and closing to end the conversation. Aside from a small number of students having trouble following etiquette, challenges appeared mostly when educators did not set clear rules on what they expected regarding WhatsApp communication. Educators have lower expectations on WhatsApp use in non-academic context.